Analisis Motivasi Kerja antara Pegawai Tetap dan Pegawai Kontrak pada Badan Nasional Penanggulangan Bencana Kota Bima - Nurkaidah Nurkaidah; Wulandari Wulandari (Universitas Serambi Mekkah, 2023)
Work motivation is the most important element that employees must have in the world of work because motivation is not only a driving force but also directs and strengthens employee behavior and performance. This research aims to determine and analyze work motivation between permanent employees and contract employees at the Bima City National Disaster Management Agency. This type of research is comparative. The research instrument used was a Likert scale questionnaire. The population used in this research was all employees of the Bima City National Disaster Management Agency, totaling 62 employees and the sample used was 30 permanent employees and 30 contract employees. The sampling technique was carried out using the quota sampling method. Data was collected by means of observation, questionnaires and literature study. Data analysis techniques use validity test, reliability test and independent sample t-test. The research results show that there is a significant difference in work motivation between permanent employees and contract employees at the Bima City National Disaster Management Agency.